1992
DOI: 10.1113/jphysiol.1992.sp019365
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ventricular end‐diastolic and systolic pressures on action potential and duration in anaesthetized dogs.

Abstract: SUMMARY1. Although it is known that mechanical events in the heart influence the duration of the cardiac action potential, there is no quantitative information on the effects of independent changes in ventricular end-diastolic and systolic pressures.2. Experiments were carried out on open-chest anaesthetized dogs in which the autonomic nervous influences on the heart were prevented and monophasic action potentials were recorded from the epicardial surface of the left ventricle. The duration of these action pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…It is possible that mental stress affected TWA in part through mechanoelectrical feedback, as changes in afterload can alter ventricular refractoriness. 44 While ischemia invokes TWA in animals, 45 as well as humans during coronary angioplasty, 45,46 in this study no ECG changes were seen, and a recent study 13 showed no correlation between stress-induced TWA changes and ischemia on SPECT. This suggests that mental stress-induced TWA is not ischemically mediated.…”
Section: Potential Pathways Linking Psychological Stress and Repolaricontrasting
confidence: 41%
See 1 more Smart Citation
“…It is possible that mental stress affected TWA in part through mechanoelectrical feedback, as changes in afterload can alter ventricular refractoriness. 44 While ischemia invokes TWA in animals, 45 as well as humans during coronary angioplasty, 45,46 in this study no ECG changes were seen, and a recent study 13 showed no correlation between stress-induced TWA changes and ischemia on SPECT. This suggests that mental stress-induced TWA is not ischemically mediated.…”
Section: Potential Pathways Linking Psychological Stress and Repolaricontrasting
confidence: 41%
“…TWA changes also correlated strongly with increases in systolic BP. It is possible that mental stress affected TWA in part through mechanoelectrical feedback, as changes in afterload can alter ventricular refractoriness 44 …”
Section: Discussionmentioning
confidence: 99%
“…The duration of the cardiac action potential is influenced by the mechanical loading conditions of the heart, a process termed ‘contraction–excitation feedback’ (Laboratory, 1982). Elevation of left ventricular peak systolic pressure was found to shorten the monophasic action potential in the heart (Coulshed et al 1992). Therefore, this mechanism is worth further investigation for its role in the production of cTnT‐ND in the responses of both ventricles to one sided pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have been studied in several in vitro and in vivo experimental studies. In contrast, after autonomic denervation in anesthetized dogs, the elevation in end diastolic pressure has been reported to increase the left ventricular MAP duration [8]. These apparently conflicting results may be due to the experimental protocol used and to the complex regulation of the mechanoelectric feedback mechanism.…”
Section: Effects Of Volume Loadingmentioning
confidence: 94%